1991
DOI: 10.1037/0882-7974.6.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Adult age differences in elaborations produced during prose recall.

Abstract: This study focused on adult age differences in the characteristics and quantity of elaborations produced during a prose recall task. Young (M = 24.3 years) and older (M = 67.9 years) adults were tested in 3 same-age, same-gender group size conditions: individual, dyad, and tetrad. Elaborations, which are statements not contained in the text but not inconsistent with it, were divided into 2 major categories. Denotative elaborations included statements that were closely related to the text and filled in gaps in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
73
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 14 publications
7
73
0
Order By: Relevance
“…In contrast, young adults may attempt to reproduce the story as accurately as possible" (Smith et al, 1983, p. 195). In a similar vein, Gould et al (1991) found a preference for annotative evaluations---that is, elaborations not directly text-based, but subjective and evaluative--in older vs. younger adults' recall of a prose passage. Conversely, there were no age differences in denotative elaborations, which are more closely text-based.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, young adults may attempt to reproduce the story as accurately as possible" (Smith et al, 1983, p. 195). In a similar vein, Gould et al (1991) found a preference for annotative evaluations---that is, elaborations not directly text-based, but subjective and evaluative--in older vs. younger adults' recall of a prose passage. Conversely, there were no age differences in denotative elaborations, which are more closely text-based.…”
mentioning
confidence: 82%
“…come from a variety of sources (Adams, 1991;Adams, Labouvie-Vief, Hobart, & Dorosz, 1990;Arbuckle & Harsany, 1985;Gould, Trevithick, & Dixon, 1991;Greenlief, Smith, & Smith, 1985). As explanation, Smith, Rebok, Smith, Hall, & Alvin (1983) have suggested that older adults' preference for a reconstructive strategy reflects a stylistic choice and not compensation for a deficit because their older subjects produced the greatest number of elaborations on passages recalled the best; in contrast, their young adult subjects produced elaborations on material with which they had the greatest difficulty.…”
mentioning
confidence: 98%
“…At Time 2, the old-old adults maintained a relatively high proportion of main idea recall, but marginally diminished levels of detail recall. Several observers have noted that older adults may actively focus narrative recall attention on superordinate ideas as a means of compensating for decrements in overall recall (e.g., Gould, Trevithick, & Dixon, 1991). Not yet known, but deserving further investigation, is whether such adaptive mechanisms originate in deliberate or strategic efforts or whether the phenomenon is linked to aging-sensitive differential recall-enhancing features of structural elements in prose passages.…”
Section: Discussionmentioning
confidence: 99%
“…At the group level, the combined output of a collaborative group is compared with the performance of a single individual. Dixon and his colleagues (e.g., Dixon, 1996Dixon, , 1999Gould, Trevithick, & Dixon, 1991) have shown that collaboration, as measured at the group level, benefits older adults' retention for previously studied material, relative to individual performance. That is, groups of older adults perform better than individual older adults in recalling a total set of previously experienced events.…”
mentioning
confidence: 99%